Dyslexic children are sluggish in disengaging spatial attention. (6th March 2019) - Fu, Wanlu; Zhao, Jing; Ding, Yun; Wang, Zhiguo
Abstract : Previous work has shown that inefficient attentional orienting is likely a causal factor for dyslexia; however, the nature of this attentional dysfunction remains unclear. The process of attentional orienting is characterized by an early facilitation effect, resulting from the successful engagement of attention, and a later inhibitory effect—frequently referred to as inhibition of return (IOR)—which encourages attentional disengagement and facilitates efficient visual sampling. The present study examined the time course of attentional orienting in dyslexic and typically developing children, by parametrically manipulating the cue‐target onset asynchronies in a spatial cueing task. Experiment 1 revealed an early facilitation effect in dyslexic children, suggesting that they have no issue in engaging attention to salient spatial locations. However, contrast to both age‐matched and reading level‐matched healthy controls, no reliable IOR effect was observed in dyslexic children, suggesting that they have difficulties in disengaging attention. When a second cue was presented to encourage attentional disengagement in Experiment 2, reliable IOR effects were observed in the same group of dyslexic children, and importantly, the onset time of IOR was comparable with that in healthy controls. These results clearly show a selective impairment of attentional disengagement in dyslexic children and provide a solid empirical basis for intervention programmes focusing on attentional shifting.